Where did they go?: Modernity and indianism in "Sab" by Gertrudis Gómez de Avellaneda - Camacho, Jorge (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Early in the 19th century, Latin America obtained its independence from Spain. Cuba and Puerto Rico, however, remained part of the “mother land” until the end of that century. That did not prevent their intellectual elite, however, from rethinking the traditional ties between their countries and the metropolis. Their hope was to find something that they could use to differentiate themselves from the others. As a result an important body of ethnic literature appeared, highly contextualized and sometimes allegorical in nature that reflected upon the lives of Amerindians in Cuba. In this essay, I would like to explore the way this process started, first with José María Heredia and continued later on, with Gertrudis Gómez de Avellaneda. In his poems, written in Mexico, Heredia start reflecting on the “original races” of the Caribbean and he does it in a way that Sigmund Freud could have only characterized as “mourning”; mourning and melancholia for the death of a dear person, who becomes associated in his writings with Cuba. In the following years, la Avellaneda will do the same. But in her case, the descendants of the “original race” will reappear dressed for war, claiming vengeance, and interwoven with the desires and demands of the slaves, free blacks and mulattos that have replaced them in the fields.